2023
DOI: 10.1186/s12879-023-08535-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning pipeline for blood culture outcome prediction using Sysmex XN-2000 blood sample results in Western Australia

Benjamin R. McFadden,
Timothy J. J. Inglis,
Mark Reynolds

Abstract: Background Bloodstream infections (BSIs) are a significant burden on the global population and represent a key area of focus in the hospital environment. Blood culture (BC) testing is the standard diagnostic test utilised to confirm the presence of a BSI. However, current BC testing practices result in low positive yields and overuse of the diagnostic test. Diagnostic stewardship research regarding BC testing is increasing, and becoming more important to reduce unnecessary resource expenditure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Within this context, three studies utilized the publicly available Medical Information Mart for Intensive Care (MIMIC) database [41, 44, 48], while four studies included Complete Blood Count/Differential Count (CBC/DC) data [24, 25, 34, 40]. Furthermore, two of these studies also incorporated Cell Population Data (CPD) [24, 40], highlighting the integration of detailed hematologic parameters. Unstructured data utilization was observed in one study that utilized textual data [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context, three studies utilized the publicly available Medical Information Mart for Intensive Care (MIMIC) database [41, 44, 48], while four studies included Complete Blood Count/Differential Count (CBC/DC) data [24, 25, 34, 40]. Furthermore, two of these studies also incorporated Cell Population Data (CPD) [24, 40], highlighting the integration of detailed hematologic parameters. Unstructured data utilization was observed in one study that utilized textual data [23].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of data accessibility, most studies employed proprietary hospital data. Data sharing policies varied: one study explicitly stated that their data would not be shared [47], one study offered openly available data [34], and ten studies indicated that deidentified data could be provided upon reasonable request [24, 25, 27, 28, 29, 38, 39, 41, 42, 49], thus contributing to transparency and reproducibility. Notably, six articles did not specify the number of patients included in their analysis [22, 24, 25, 28, 31, 48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two models evaluated in this study were trained in our previous study 19 . The XG model was trained using CBC, DIFF, and CPD features with boruta feature selection (BFS) and 1.5 class weights in favour of the positive BC result; and the RF model was trained using CBC and DIFF features, BFS, and balanced class weights.…”
Section: Machine Learning Pipelinementioning
confidence: 99%
“…In our previous work, we developed a ML pipeline for BC outcome prediction which achieved promising results using models trained with complete blood count (CBC), white blood cell differential (DIFF), and cell population data (CPD). 19 . In this study, we further validated this pipeline using a prospectively collected ED dataset.…”
Section: Introductionmentioning
confidence: 99%